2020
DOI: 10.1007/s00128-020-02937-3
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nitrogen Dioxide (NO2) from Vehicular Emission Could Increase the COVID-19 Pandemic Fatality in India: A Perspective

Abstract: The corona virus-2019 (COVID-19) is ravaging the whole world. Scientists have been trying to acquire more knowledge on different aspects of COVID-19. This study attempts to determine the effects of COVID-19, on a large population, which has already been persistently exposed to various atmospheric pollutants in different parts of India. Atmospheric pollutants and COVID-19 data, obtained from online resources, were used in this study. This study has shown strong positive correlation between the concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 17 publications
(17 reference statements)
2
38
2
2
Order By: Relevance
“…Cole et al (2020) go further by offering evidence that certain municipalities in the Netherlands with 1 μg/m3 more PM 2.5 concentrations suffered 9.4 more COVID-19 cases, 3.0 more hospital admissions, and 2.3 more deaths. In the same vein, Chakraborty et al (2020) concluded that exposure to vehicle NO 2 emissions increased COVID-19 fatality in India. The authors argue that homeless, poverty-stricken Indian hawkers and roadside vendors, as well as individuals suffering regular exposure to the exhaust of vehicles, may be at a higher risk.…”
Section: Resultsmentioning
confidence: 97%
“…Cole et al (2020) go further by offering evidence that certain municipalities in the Netherlands with 1 μg/m3 more PM 2.5 concentrations suffered 9.4 more COVID-19 cases, 3.0 more hospital admissions, and 2.3 more deaths. In the same vein, Chakraborty et al (2020) concluded that exposure to vehicle NO 2 emissions increased COVID-19 fatality in India. The authors argue that homeless, poverty-stricken Indian hawkers and roadside vendors, as well as individuals suffering regular exposure to the exhaust of vehicles, may be at a higher risk.…”
Section: Resultsmentioning
confidence: 97%
“…Only four studies investigated the link between NO 2 and COVID-19 related mortality, as shown in Table 1 , where Chakraborty et al (2020) focused on 18 Indian States, Filippini et al (2020) on 28 provinces of Northern Italy, Yao et al (2020) on 63 Chinese cities, Ogen (2020) for 66 administrative regions among four European countries (Italy, Spain, France and Germany).…”
Section: Literature Reviewmentioning
confidence: 99%
“… Chakraborty et al (2020) attempted to determine the effect of NO 2 concentration on COVID-19 deaths and case fatality rate in 18 Indian States. Empirical results showed that both associations are statistically significant and positive, indicating that homeless, poverty-stricken Indians, roadside vendors and many others who are regularly exposed to vehicular exhaust, may be at a higher risk in the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…What's more, the PM 2.5 exhibited positive association (relative risk (RR) = 1.079, 95%CI 1.071–1.086, p < 0.01) with COVID-19 deaths, while the temperature was inversely associated with COVID-19 deaths (RR = 0.861, 95%CI 0.851–0.872, p < 0.01) based on the daily COVID-19 death number, air quality index (AQI), ambient air pollutant concentrations, and meteorological variables data of Wuhan between Jan 25 and April 7, 2020 ( Jiang and Xu, 2020 ). There is a strong positive correlation between the concentration of atmospheric nitrogen dioxide (NO 2 ) and both the absolute number of COVID-19 deaths (r = 0.79, p < 0.05) and case fatality rate (r = 0.74, p < 0.05) in India ( Chakraborty et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%